Rasga Coração, de Vianinha, e Hair: aproximação e distanciamento num contexto de contracultura - Éwerton Silva de Oliveira (Universidade de Brasília, 2015)
Considering the plays’ formal and content structure, and the political and cultural movements of the 60’s and 70’s youth  the counterculture among them  in the North - American context and in the B razilian historical process (including the dictatorship present in Brazil in these decades), this article aims to analyze how the musical called Hair (1967), by the American actors James Rado and Gerome Ragni, and Rasga coração (1974), a play by the Brazil ian playwright Oduvaldo Vianna Filho (Vianinha), represent the presence of the counterculture, with its innovations and contradictions, similarities and differences, in Brazil and in the United States. This representation is made especially by the young ch aracters of these plays, and the different focus Rasga coração and Hair give to this political - cultural movement is also emphasized in the article.